2021
DOI: 10.1002/aelm.202100782
|View full text |Cite
|
Sign up to set email alerts
|

Magnonic Goos–Hänchen Effect Induced by 1D Solitons

Abstract: the chiral solitons of monoaxial helimagnets. These solitonic states appear easily in chiral magnets, characterized by the presence of an important Dzyaloshinskii-Moriya interaction (DMI). Domain walls and their magnonics, with and without DMI, are being extensively studied. [4][5][6][7][8][9][10][11][12] Comparatively, monoaxial helimagnets, in which the DMI acts only along one axis (the DMI axis), have received much less attention, although many experimental and theoretical results concerning their equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…Spin waves are also scattered by magnetic solitons like domain walls [33], skyrmions [34] or one dimensional chiral solitons [35], producing effects that could also be useful to control the spin waves. For instance, the scattering by a one dimensional soliton causes a lateral shift of the propagation direction of the scattered waves analogous to the Goos-Hänchen displacement [35]. It has been proposed that the scattering by domain walls can be used for spin wave interferometry [36] or as a spin wave valve [37].…”
Section: Introductionmentioning
confidence: 99%
“…Spin waves are also scattered by magnetic solitons like domain walls [33], skyrmions [34] or one dimensional chiral solitons [35], producing effects that could also be useful to control the spin waves. For instance, the scattering by a one dimensional soliton causes a lateral shift of the propagation direction of the scattered waves analogous to the Goos-Hänchen displacement [35]. It has been proposed that the scattering by domain walls can be used for spin wave interferometry [36] or as a spin wave valve [37].…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, by symmetry the shift at normal incidence should vanish in the case of a 360 o wall, and indeed it has been shown that it does vanish in the case of the chiral soliton of monoaxial helimagnets 35 . But symmetry is absent in the case of the 180 o domain wall considered here, since the spin wave propagates between two domains with opposite magnetizations.…”
Section: A the X → ∞ Asymptoticsmentioning
confidence: 95%
“…We will discuss this in further quantitative detail in what follows below. It is interesting to note here that the Goos-Hänchen effect (GHE) has been recently encountered not only in the context of solitary waves interacting with external potentials but also of linear waves interacting with solitary ones [34].…”
Section: B Goos-hänchen Shifts Of Reflection Upon Potential Wallsmentioning
confidence: 99%